2020
DOI: 10.21615/cesp.14.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factor Structure of Environmental Attitudes Measure in a Sample of Indonesian College Students

Abstract: The purpose of this study was to validate and evaluate the factor structure of the instrument for measuring attitudes towards the environment using factor analysis and multidimensional polytomous Rasch model. Participants in this study were 595 Indonesian university students (293 male and 302 female) with an age range of 18-24 (mean age = 21.01, SD = 1.65). The 22-items of Environmental Attitudes Measure were administered using online survey systems. This study generates a three-dimensional factor structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
0
0
1
Order By: Relevance
“…Se han creado diversas herramientas de evaluación que desempeñan un papel fundamental en la recopilación y el análisis de datos sobre las actitudes de una población hacia el MA, los cuales son cruciales para comprender cómo las personas perciben y valoran su entorno natural, así como para identificar posibles barreras y motivaciones que puedan influir en su comportamiento hacia la protección del MA (Hayat et al, 2021;Herrera Mendoza et al, 2016). Entonces para examinar el impacto que generan las intenciones de comportamiento ambiental sobre las actitudes ambientales en estudiantes de ingeniería e ingenieros activos, se propone la siguiente hipótesis: H1: Las actitudes ambientales tienen un efecto directo y positivo en las intenciones de comportamiento ambiental.…”
Section: Relación De Actitudes E Intenciones Ambientalesunclassified
“…Se han creado diversas herramientas de evaluación que desempeñan un papel fundamental en la recopilación y el análisis de datos sobre las actitudes de una población hacia el MA, los cuales son cruciales para comprender cómo las personas perciben y valoran su entorno natural, así como para identificar posibles barreras y motivaciones que puedan influir en su comportamiento hacia la protección del MA (Hayat et al, 2021;Herrera Mendoza et al, 2016). Entonces para examinar el impacto que generan las intenciones de comportamiento ambiental sobre las actitudes ambientales en estudiantes de ingeniería e ingenieros activos, se propone la siguiente hipótesis: H1: Las actitudes ambientales tienen un efecto directo y positivo en las intenciones de comportamiento ambiental.…”
Section: Relación De Actitudes E Intenciones Ambientalesunclassified
“…In addition, previous studies outside Indonesia have also reported the psychometric properties of this instrument using the confirmatory factor analysis method eg, (Seneca, 2006)). However, based on a review of the existing literature, there has been no research in either Indonesia or other countries that examines the psychometric properties of materialistic personality scales using modern test theory approaches such as the IRT or the Rasch model, though it has been well known that the development of modern test theory was carried out to overcome the limitations of Classical Test Theory (Hayat et al, 2021).…”
mentioning
confidence: 99%
“…The Rasch model (Wolins, 1982) is one of the modern test theory approaches that has contributed greatly to research in the field of psychology (Aryadoust et al, 2019). With the application of the Rasch model, psychometric property testing will produce more in-depth item analysis results when compared to the classical approach (Hayat et al, 2021). In addition, the Rasch model can produce linear measurement results between respondents and items so that the interrelationships between the two can be compared directly with each other (Andrich, 1978;Sumintono & Widhiarso, 2014).…”
mentioning
confidence: 99%